The Immunohistochemical Prognostic Value of Nuclear and Cytoplasmic Silent Information Regulator 1 Protein Expression in Saudi Patients with Breast Cancer - Bayan Alharbi; Alia Aldahlawi; Mourad Assidi; Fatemah Basingab; Kawther Zaher; Jehan Alrahimi; Sara Mokhtar; Jaudah Al-Maghrabi; Abdelbaset Buhmeida; Kaltoom Al-Sakkaf (Biomolecules)
Background: The mammalian NAD-dependent deacetylase sirtuin-1 family (named also silent information regulator or SIRT family, where NAD stands for “nicotinamide adenine dinucleotide” (NAD)) appears to have a dual role in several human cancers by modulating cell proliferation and death. This study examines how SIRT1 protein levels correlate with clinicopathological characteristics and survival outcomes in patients with breast cancer. Methods: A total of 407 BC formalin-fixed paraffin-embedded (FFPE) samples were collected from King Abdulaziz University Hospital, Saudi Arabia. SIRT1 was stained on tissue microarray slides using automated immunohistochemistry. Results: All BC subtypes expressed more nuclear SIRT1 proteins than their cytoplasm counterparts. In luminal A, luminal B, and TNBC, nuclear and cytoplasmic SIRT1 were highly associated (p < 0.001). Kaplan–Meier analysis showed reduced disease-specific survival (DSS) in H2BC with high SIRT1 nuclear expression (p = 0.001, log-rank). Moreover, the cytoplasmic expression of SIRT1 in HER2-positive BC was associated with a larger tumor size (p = 0.036) and lymph node metastasis (p = 0.045). Nuclear SIRT1 expression was also positively associated with lymph node metastasis (LNM) (p = 0.048). As low-grade tumors had a higher frequency of SIRT1 protein expression than other groups, SIRT1 expression was associated with a favorable prognosis in patients with luminal A BC (p < 0.001). Conclusions: SIRT1 expression seems to be involved in different molecular pathways either suppressing or promoting tumor growth depending on the subtype of BC. These molecular functions require further investigations and validation on larger BC cohorts.